Recuperação de amônia por irradiação de micro-ondas e air stripping em água residuária de curtume - Rios, Carlos Alberto Segatto (2015)
Nitrogenous compounds from liquid effluents from tannery have a high pollution potential and are generated mainly in the leather deliming process. While maintaining complex wastewater treatment systems, there may be difficulties in meeting the discharge standards of 20 mg N-NH3, provided by the Brazilian Environmental Legislation. This research sought to contribute to the development of alternative technologies applied to the removal of ammonia present in the effluent from the deliming process, followed by nitrogen recovery in scrubber. In the first step, 30 experiments were performed with microwave irradiation for 1 min at 700 W domestic microwave adapted and 4 min aeration, following statistical design type Rotatable Central Composite Design (RCCD). It was varied in irradiation power (Pot.%), air flow (Qar), initial pH (pH), and dilution of the effluent (Conc.). The maximum ammonia removal efficiency was 94,9% with 80% irradiation power, air flow 1,5 L min-1, pH 12 and dilution of the effluent 60%. Nitrogen recovery in the gas washer (sulfuric acid solution 0,2 M) was close to 100%. In the second stage, it was performed 20 experiments (RCCD) using air stripping tower changing the air flow (Qar), effluent flow (Qliq.) and initial pH (pH). The maximum efficiency of ammonia removal was 84,3% with airflow 2400 L min-1, effluent flow 0,6 L min-1 and pH 11,4. Scrubber, constituted by recirculation and continuous countercurrent sulfuric acid solution 0,1 M, recovered to 55% of nitrogen. The pH decisively influenced the performance of the two systems tested, with the best values in the range 11,4 to 12,0.